Sponge Fishing in Twentieth-century Cyprus: A Multidisciplinary Appraisal of a Story of Non-success - Ktori, Maria (Journal for the History of Environment and Society, 2024)
Abstract Cyprus’ rich sponge beds have attracted sponge divers from the Dodecanese since the mid-nineteenth century, but they have not attracted the Cypriots’ attention. As the island transitioned from Ottoman to British hands, the British decided to organize the “Cypriot sponge industry” and train Cypriots, hoping to end the Greek monopoly over the island’s sponge beds. The author combined historical, legislative, and ethnoarchaeological data to: a) clarify the historical evolution of this profession during British colonial rule, b) present an understanding of underwater hazards from three viewpoints (colonial government, Greek sponge divers, and Cypriot non-divers), c) determine how colonial policies influenced maritime labour, and d) ascertain whether the British succeeded in creating a nucleus of local sponge divers. Evidence shows that few Cypriots practiced sponge fishing even after the establishment of the Republic of Cyprus in 1960. Their weak relationship with this specific maritime profession did not improve after the advent of scuba, and the last Cypriot sponge diver retired in 1986.
Keywords: sponge fishing